2021
DOI: 10.1186/s13071-021-05018-4
|View full text |Cite
|
Sign up to set email alerts
|

The potential risk of enzootic Trypanosoma cruzi transmission inside four training and re-training military battalions (BITER) in Colombia

Abstract: Background Colombia’s National Army is one of the largest military institutions in the country based on the number of serving members and its presence throughout the country. There have been reports of cases of acute or chronic cases of Chagas disease among active military personnel. These may be the result of military-associated activities performed in jungles and other endemic areas or the consequence of exposure to Trypanosoma cruzi inside military establishments/facilities located in endemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 64 publications
3
20
0
Order By: Relevance
“…The municipalities of Chinavita, Garagoa and Sutatenza were certified free of R. prolixus intradomiciliary T. cruzi transmission in 2017 by PAHO, while Guateque, Somondoco and Tenza will be evaluated for certification in 2022 by PAHO. From each municipality, villages with household with T. venosa infestation reports after chemical-intervention for elimination of R. prolixus were selected for evaluation ( Table 1 ) ( Cantillo-Barraza et al., 2021 ). In addition, Triatomine Collection Stations (PITs-acronym in Spanish) for regular community surveillance activities were installed at each study location, as described by Cantillo-Barraza ( Cantillo-Barraza et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The municipalities of Chinavita, Garagoa and Sutatenza were certified free of R. prolixus intradomiciliary T. cruzi transmission in 2017 by PAHO, while Guateque, Somondoco and Tenza will be evaluated for certification in 2022 by PAHO. From each municipality, villages with household with T. venosa infestation reports after chemical-intervention for elimination of R. prolixus were selected for evaluation ( Table 1 ) ( Cantillo-Barraza et al., 2021 ). In addition, Triatomine Collection Stations (PITs-acronym in Spanish) for regular community surveillance activities were installed at each study location, as described by Cantillo-Barraza ( Cantillo-Barraza et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Boyacá department has 24 municipalities recently certified by PAHO-WHO as free of T. cruzi transmission through the elimination of intradomiciliary R. prolixus ( Cantillo-Barraza et al., 2021 ; Velásquez-Ortiz et al., 2022 ). However, recent evidence suggests that T. cruzi transmission risk maintained by other triatomine species, considering they can take advantage of the available niche, following the R. prolixus elimination ( Cantillo-Barraza et al., 2020a ; Cantillo-Barraza et al., 2021 ). The Tenza Valley, located in the southwest of the department, is a subregion Included in the elimination initiative ( Corredor et al., 1990 ; Guhl et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, anti-T. cruzi antibodies were detected in 50% (17/34) of dogs from two rural settlements in the Sierra de Los Tuxtlas, Veracruz, Mexico [44]. In Costa Rica, 5.2-27.7% of dogs were seropositive in endemic areas [45][46][47], whereas in Colombia the prevalence ranged from 9.6% to 34% [48][49][50][51][52]. In the US, a study with 86 working dogs reported a seroprevalence of 14.1% [53], whereas other studies reported a lower prevalence [54][55][56][57].…”
Section: Trypanosoma Cruzi Infection and CD In Dogsmentioning
confidence: 99%